Creep effects on tension-tension fatigue behavior of angle-ply GFRP composite laminates. (June 2019) - Movahedi-Rad, A. Vahid; Keller, Thomas; Vassilopoulos, Anastasios P.
Highlights: Creep-fatigue interaction in (±45)2s glass/epoxy composite laminates was studied. Fatigue loading was interrupted by creep at the maximum stress level. Fatigue behavior was affected by hold loads (creep). Damage was observed at the early stages of pure creep. Fatigue damage accelerated the creep strain development during the hold time. Abstract: Angle-ply (±45)2S glass/epoxy composite specimens have been subjected to pure creep and tension-tension constant amplitude fatigue loading interrupted at σmax by creep intervals lasting for 2 or 48 h in order to examine the effects of creep loading on the fatigue response and vice versa. The specimens' behavior and damage status were continuously monitored during the experiments; strains were measured by a video extensometer, the self-generated temperature on the specimens' surface was recorded by an infrared camera, while a digital camera with sufficient backlighting was used in order to capture the damage development in the translucent specimens throughout the experiment. Post-mortem photos were taken by a digital microscope for the analysis of the fracture surfaces. In comparison to continuous fatigue, applying the creep-fatigue loading pattern with a 2-h creep time at low stress levels had no effect on fatigue life. However, as the stress level increased, specimen stiffening occurred during creep loading because of the glass fiber realignment, which also decreased the internal friction, hysteresis loop area, and self-generated temperature, thus prolonging the fatigue life. The restoring of fatigue stiffness was greater at a creep time of 48 h due to more creep strain, which led to more fiber realignment. However, the higher creep strain at high stress levels caused more creep damage and thus resulted in a shorter fatigue life. In addition, it was observed that the fatigue damage accelerated creep deformation.